Integrating Soil Physicochemical Properties and Microbial Functional Prediction to Assess Land-Use Impacts in a Cold-Region Wetland Ecosystem - Junnan Ding; Shaopeng Yu (Life, 2025)
This study investigated the effects of land-use change and wetland restoration on soil microbial community diversity, structure, and function in a cold-region wetland ecosystem. Soil samples from six land-use types were analyzed for key physicochemical and biochemical properties, including soil water content, pH, total nitrogen, soil organic carbon (SOC), and enzymatic activities. Significant differences in carbon and nitrogen availability were observed, with restored wetland soils showing higher SOC and moisture levels, while agricultural soils exhibited elevated nitrate concentrations. Bacterial community composition was estimated based on 16S ribosomal RNA gene sequencing, and microbial functional profiles were predicted using Functional Annotation of Prokaryotic Taxa (FAPROTAX) and BugBase. Bacterial communities were dominated by Proteobacteria, Actinobacteriota, and Acidobacteriota, with significant shifts among land-use types. Redundancy analysis revealed that SOC, SWC, total nitrogen (TN), and pH were key drivers of community differentiation. Functional prediction showed enrichment of fermentation and anaerobic metabolism in restored wetlands, while aerobic carbon metabolism dominated in agricultural and forest soils. These findings demonstrate that wetland restoration improves both taxonomic and functional diversity. While ecosystem multifunctionality and resilience were not directly quantified, the observed increases in microbial richness, functional group diversity, and enzymatic activity suggest enhanced ecological capacity and potential for system stability in cold-region wetlands.